1997
DOI: 10.1046/j.1365-2796.1997.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Does metformin increase the serum total homocysteine level in non‐insulin‐dependent diabetes mellitus?

Abstract: Abstract. Hoogeveen EK, Kostense PJ, Jakobs C, Bouter LM, Heine RJ, Stehouwer CDA (Vrije Universiteit, Amsterdam, the Netherlands). Does metformin increase the serum total homocysteine level in non-insulin-dependent diabetes mellitus? J Intern Med 1997; 242: 389-94.Objective. The aim of this study was to estimate the effect of metformin on the serum total homocysteine level in non-insulin-dependent diabetes mellitus (NIDDM) patients. An elevated serum total homocysteine level is a risk factor for atheroscleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
4
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 35 publications
(51 reference statements)
5
39
4
3
Order By: Relevance
“…Carlsen et al (49) reported that metformin therapy was associated with increased tHcy levels in nondiabetic subjects with cardiovascular disease. However, we found no significant difference between plasma tHcy concentrations in metformin-treated and non-metformintreated diabetic patients, in accordance with Hoogeveen et al (50).…”
Section: Homocysteine In Type 2 Diabetessupporting
confidence: 93%
“…Carlsen et al (49) reported that metformin therapy was associated with increased tHcy levels in nondiabetic subjects with cardiovascular disease. However, we found no significant difference between plasma tHcy concentrations in metformin-treated and non-metformintreated diabetic patients, in accordance with Hoogeveen et al (50).…”
Section: Homocysteine In Type 2 Diabetessupporting
confidence: 93%
“…Several previous studies reported that metformin has no effect on homocysteine or small effect, if any [4, [25][26][27]. However, patients using metformin without vitamin B 12 supplementation in the present study showed high prevalence of vitamin B 12 deficiency.…”
Section: Resultscontrasting
confidence: 58%
“…Even after further adjustment for past history of cardiovascular events and intake of metformin, one of the Table 3 Correlations with serum total homocysteine concentration level in diabetics and non-diabetic subjects according to multiple regression analysis important agents affecting tHcy [33], all the above results were basically unchanged (data were not shown).…”
Section: Resultsmentioning
confidence: 97%